The Alleviation of Discoloration in Teak (Tectona grandis L.f.) Wood Through Drying and Chemical Treatments - Efrida Basri; Dede Rohadi; Trisna Priadi; Imam Wahyudi (Masyarakat Peneliti Kayu Indonesia, 2004)
Teak wood is well known as one of the important wood species from Indonesia. The properties of this wood are quite good and delighted by many people. However, the wood processing may cause discoloration on some pieces or boards of this wood. This degrades the wood performance. The wood surface is slightly darkened. Dark-brown streaks often arise distinctly on the brown color of wood surface. Moreover, when the kiln-dried wood is re-exposed in the further process with a planner or a molder, the discoloration may still exist. The aim of this study was to find out an appropriate technique to alleviate discoloration on teak wood. The result showed that drying temperature was the most important factor in the discoloration of teak wood. Among chemical treatments in this experiment, the use of 3% Na2SO3 solution was the most effective way to alleviate discoloration on teak wood